Pengaruh Pelatihan dan Pengembangan Karir Terhadap Kinerja Karyawan di PT Telkom Indonesia Witel Bekasi - Rahmadianti, Rosi Novita; Syarif, Mahmud; Anggarini, Desy Tri (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
PT Telkom Indonesia is Witel Bekasi, one of the leading telecommunications companies in Indonesia, committed to developing human resources to provide excellent customer service. The purpose of this study was to determine the effect of training and career development on employee performance at PT Telkom Indonesia Witel Bekasi. The population in this study were all employees of PT Telkom Indonesia Witel Bekasi and the number of samples used was 33 respondents. The data collection technique used was non-probability sampling with saturated sampling technique. The approach method in this study used a quantitative method with data collection through research instruments. The data analysis techniques used are instrument test, descriptive analysis, classical assumption test, multiple linear regression analysis, coefficient of determination test, and hypothesis test using SPPS 27. The results of this study t_value (calculated) 2.137 t_(table) 2.042 with a significance level of 0.041 0.05 that training has a positive and significant effect on employee performance, while career development t_value (calculated) 2.106 t_(table) 2.042 with a significance level of 0.044 0.05 has a positive and significant effect on employee performance. Simultaneously f_value (calculated) 5.088 f_(table) 3.316 with a significance level of 0.013 0.05 training and career development have a positive and significant effect on employee performance.